Current Scenario of the Small-scale Broiler Farming in Bangladesh: Potentials for the Future Projection - Islam, Md. Saiful; Takashi, Sasaki; Chhabi, Kaniz Quamrun Nahar (International Journal of Poultry Science, 2010)
In Bangladesh, there are two types of broiler farming of which contract broiler farming is still under trial while independent small-scale broiler farming is dominant and performed for the development of broiler sector. The present study examined the potentials of small-scale independent broiler farms and farmers’ economic behavior in relation to farm size. Farm size is found to be closely related to farmers’ behavior and attitude. Farmers’ behavior and attitude appeared to be very crucial factor for the development of broiler production. The primary data were collected from the independent small-scale farms in Mymensingh district of Bangladesh. The results showed that independent small-scale broiler farming is a profitable venture for rural farmers. Farmers are involving in this sector because of lower investment, less space requirement, utilization of family labor and quick returns. To examine the farmers’ behavior, farmers were classified into two income goal groups in terms of total per capita income: a) First Income Goal Group (FIGG) and b) Second Income Goal Group (SIGG). The economic behaviors of the farmers were differed by income goal groups. Most of the farmers belonging to the FIGG were interested to enlarge their farm size, the opposed trend has been observed in farmers of SIGG. Economic behavior and attitude should be considered in making any suggestion and recommendation for changing the existing level of small-scale broiler farming.